Healthcare planning across healthcare sectors in Baden-Wuerttemberg, Germany: a stakeholder online survey to identify indicators - Wronski, Pamela; Koetsenruijter, Jan; Ose, Dominik; Paulus, Jan; Szecsenyi, Joachim; Wensing, Michel (BMC health services research, 2021)
Stakeholders in the German state of Baden-Wuerttemberg agreed upon the central aims for healthcare planning. These include a focus on geographical districts; a comprehensive, cross-sectoral perspective on healthcare needs and services; and use of regional data for healthcare planning. Therefore, healthcare data at district level is needed. Nevertheless, decision makers face the challenge to make a selection from numerous indicators and frameworks, which all have limitations or do not well apply to the targeted setting. The aim of this study was to identify district level indicators to be used in Baden-Wuerttemberg for the purpose of cross-sectoral and needs-based healthcare planning involving stakeholders of the health system.